219k views
5 votes
Convert into slope-intercept form:
y-1=m(x-3)

2 Answers

1 vote

Answer:

y = 2x - 5

Explanation:

y - 1 = 2(x - 3)

y - 1 = 2x - 6

y - 1 + 1 = 2x -6 + 1

y = 2x - 5

User RJ Adriaansen
by
5.7k points
4 votes

Answer:

y=2x-5

Explanation:

First simplify: y-1=2x-6

y-1=2(x-3)

First simplify and distribute everything.

y-1=2x-6

So, x equals 2 because it got distributed into the numbers inside the parenthesis. Same with the 2 and -3. They multiplied to become -6.

Since it's y-1=2x-6, you can simplify it even more so the -1 goes to the other side and turns into positive 1.

y - 1 (+ 1) = 2x -6 (+ 1)

-1(+1)=0 which leaves just the variable y on the left side.

-6(+1)=-5 which leaves 2x-5 on the right side.

This results in y=2x-5. Hope this helped ;)

User Thiago Valente
by
5.8k points